KEBIJAKAN MODAL MINIMUM, KEBIJAKAN KEPEMILIKAN TUNGGAL DAN PENYALAHGUNAAN POSISI DOMINAN DALAM PERSAINGAN USAHA INDUSTRI PERBANKAN - Taswan, Taswan (Benefit: Jurnal Manajemen dan Bisnis, 2011)
This paper is concerned with three issues. First, , this paper describes the policy of minimum capital and the single presence policy and its consequences on market structure.  Secondly,  abuse  of dominant position,  and the third about the steps to prevent it in order to create healthy competition in the banking industry.  The minimum core capital policy and the single presence policy is suspected to have contributed to the formation of the concentration of the banking structure or oligopoly market structure.  This could potentially lead to a dominant position. Abuse of dominant position in the oligopoly market structure could cartel prices or interest rates. The cartel is  very detrimental to consumers because consumers bear the cost of higher interest than when there  is no cartel.Therefore the Commission for the Supervision of Business Competition must act decisively and prevention efforts. The Commission for the Supervision of Business Competition  should actively perform preventive action by advising policy revision of minimum capital, single presence policy, the revision of the legal lending limit, the setting of public funds related and unrelated, it is necessary to prohibit the cross-crediting a cross between a bank, and cooperate with the Deposit Insurance Institution or LPS to create a healthy business competition in the banking industry.